ACCURACY OF PRELIMINARY DATA OBTAINED FROM TOPOGRAPHIC PLANS FOR THE DESIGN OF HYDRAULIC STRUCTURES - M. Kh. Rajapbaev (International Scientific and Current Research Conferences, 2023)
In this article, creating a topographic plan of the reservoir, determining the horizontal values of the reservoir in terms of height, establishing radial networks of the reservoir using the closed polygon method, determining coordinate values by installing receivers, and determining connecting points.